JAUNATNES EKOLOĢISKĀS IZGLĪTOŠANAS PROBLĒMAS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 1999)
Youth Ecological education is one of the most important tasks nowadays. Men’s behaesor in environment and decisions in environmental protection problems depends on their previous ecological epleuation and consciousness. It is necessary to up bring in children attitude to nature with care presents ecological code for children (and not only) containing 11 important points.